Pelaksanaan Ketentuan Hukum Pemungutan Pajak Restoran pada Kota Tangerang Selatan Berdasarkan Perda Nomor 7 Tahun 2010 tentang Pajak Daerah - Adhitiya, Arie; Saefullah, Saefullah; Artono, Harry Budi (VISA: Journal of Vision and Ideas, 2024)
The potential for restaurant tax revenue in South Tangerang City is very large, but there are several issues that cause tax revenue to be suboptimal. One of the main problems is the manipulation of tax deposits by restaurant taxpayers, which harms the local government because the tax received is lower than it should be. Research using normative legal methods shows that many restaurants still use manual recording systems that are easily manipulated. The Extensification Team must be extra careful in determining the basic tax assessment value because many taxpayers try to deceive tax inspectors by manipulating revenue records. As a result, the reported monthly income is low, so the tax paid is also low, even though the restaurant's profits are high. Law enforcement against restaurant tax violations can be carried out in two ways: administrative sanctions, such as fines and reprimands, and criminal sanctions, which can include imprisonment for significant tax manipulation offenders. With strict law enforcement, it is hoped that restaurant tax revenue in South Tangerang City can be more optimal.